Offsetting risk in a neoliberal environment: The link between asset-based welfare and NIMBYism - Matthew C. Record (Journal of Risk and Financial Management, 2021)
Affordable housing policy in the developed world has been undergoing a systematic commodification for several decades, including a push for homeownership as the normalized tenure and a commodity unto itself. Scholars suggest this push for homeownership is part and parcel of a neoliberal asset-based welfare to supplement, or even outright replace, traditionally defined benefit pension schemes. These policies individualize risk and re-fashion individual citizens as long-term financial planners, navigating the uncertainty inherent in international financial markets and general financial management. Less deeply explored, however, are the perverse incentives this system creates for homeowners to protect their home 'investment' by leveraging planning policies, zoning, and land-use restrictions to preserve the community status quo and lock in the value of their home. In a policy environment in which long-term financial risk is individualized and public social welfare and pension systems are relegated to the smallest number of individuals possible, this type of NIMBYism (Not in My Backyard) is rather rational behavior, even as it simultaneously staunches the supply of new housing and drives up prices for non-homeowners. As such, this analysis synthesizes the existing research to make a formal theoretical connection between the neoliberal push for commodified housing, asset-based welfare, and the intractable political problem of NIMBYism.
Keywords: 330; housing; pensions; risk management; commodification; neoliberalism; affordable housing; asset-based welfare; homeownership